FRI0685 The presence of rheumatoid factor is associated with lower bone mass in korean health screening male subjects without clinically apparent arthritis. (15th June 2017) - Hwang, J; Ahn, JK; Eun, YH; Park, E-J; Lee, J; Koh, E-M; Cha, H-S
Abstract : Background: Close relationship between the immune and skeletal systems has been recognized through the bone loss in rheumatoid arthritis (RA). Rheumatoid factor (RF) is present in approximately 70–80% of RA patients, which is an autoantibody directed against the Fc component of IgG and associated with osteoporosis and reduced bone mineral density (BMD) in RA. RF is also found nonspecifically in chronic inflammatory condition such as sarcoidosis, hepatitis B or C, and tuberculosis. However, the influence of RF to bone loss is scarcely known in subjects without any specific medical problem. Objectives: This cross-sectional study aimed to investigate the association between the presence of RF and BMD in Korean healthy male subjects without any history of joint disease. Methods: Of the 84, 344 males who had undergone a comprehensive health checkup program in 2012, 1, 390 healthy subjects were recruited, whose BMD and RF results were available. Subjects with history of diabetes, kidney disease, thyroid disease, and malignancy, and taking medicine regarding these diseases, osteoporosis, and arthritis were excluded based on self-reported questionnaire. The RF titer ≥20 IU/ml was considered positive. BMD was categorized into 3 groups based on T-score; normal (T-score ≥ -1.0), osteopenia (-1.0 > T-score > -2.5) and osteoporosis (T-score ≤ -2.5). The association between the presence of RF and BMD was assessed by multiple linear regression analysis. Results: Of 1, 390 males, the mean age was 52.8±10.9 years (range, 22 – 83) and RF was positive in 64 subjects (4.6%). Demographics including smoking history, alcohol consumption, the frequency of vigorous exercise and body mass index (BMI), and laboratory data were not different between RF-positive and –negative subjects except hepatitis B surface antigen, which was more frequently seen in RF-positive subjects (15.6% vs. 4.3%, p =0.001). Low bone mass (osteopenia and osteoporosis) of lumbar spine was more prevalent in subjects aged 50 or more compared with those younger than 50 years (28.0% vs. 10.7%, p <0.001) while no differences of femur neck and total hip. RF-positive subjects had significantly lower BMD compared to RF-negative subjects in lumbar spine (1.10±0.18 g/cm 2 vs. 1.17±0.16 g/cm 2, p =0.002) but neither in femur neck nor total hip. In subjects with higher titer RF (≥40 IU/ml), the mean BMD of lumbar spine was significantly decreased than those with lower titer RF (one-way ANOVA, F (3, 1190) =3.527, p =0.015). After adjusting for multiple confounders such as age, BMI, glomerular filtration rate, serum concentration of calcium, phosphorus, and uric acid, and lifestyle factors (drinking, smoking, and physical exercise), RF positivity was negatively associated with BMD at lumbar spine ( B = -0.055 and SE =0.027, p =0.039). Conclusions: Our results provide epidemiological evidence that the presence of RF could have an unfavorable impact on bone density in apparently healthy male subjects. Additional studies to elucidate the osteoimmunological mechanism of RF are warranted. Disclosure of Interest: None declared